Do consumers prefer offers that are easy to compare? An experimental investigation - Paolo Crosetto; Alexia Gaudeul (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2011)
Consumers make mistakes when facing complex purchasing decision problems but if at least some consumers choose only among offers that are easy to compare with others then firms will adopt common ways to present their offers and thus make choice easier (Gaudeul and Sugden, 2011). We design an original experiment to identify consumers' choice heuristics in the lab. Subjects are presented with menus of offers and do appear to favour offers that are easy to compare with others in the menu. While not all subjects do so, this is enough to deter firms from introducing spurious complexity in the way they present products.
Keywords: D83; L13; D18; 330; bounded rationality; cognitive limitations; common standards; consumer choice; experimental economics; heuristics; libertarian paternalism; pricing formats; spurious complexity; Konsumtheorie; Entscheidung; Vergleich; Beschränkte Rationalität; Test